PENGABAIAN ORANG TUA DALAM DUNIA DIGITAL ANAK: IMPLIKASI TERHADAP HAK ASUH MENURUT HUKUM ISLAM - Sapri Ali; Nalita Hajar Aswad (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
Digitalization brings changes in childcare, especially media and technology sources, as more and more parents allow their children to be stimulated by the presence of a shared position with the adopted position of children at various moral, social, and spiritual levels. This is a form of legal neglect of the executive parent and in the perspective of Islamic law is defined in terms of the mandate of care (ḥaḍānah). The purpose of this study is to express and detail the same problem, as well as convey information and scientific issues and opinions regarding the position of the digital world on children in this study using various library research methods and theological-normative, psychological, and sociological approaches and the rules of the Qur'an, hadith, classical books (yellow books) and Law No. 35 of 2014 concerning Child Protection, issued. This is assessed internally and externally. Digital consumption without parental supervision can influence the emergence of deviant behavior leading to vulgarity, online game addiction and disrespect towards parents. From an Islamic perspective, parents not only "own" their children physically, but also their faith, morals, and character. Therefore, minimal parental supervision of children's digital sites and applications can be considered a serious violation of legal custody. Furthermore, this study aims to raise parents' awareness of their potential educational and preventive role in the digital world, based on Islamic values, as a solution. This study is not intended to blame parents, but to reawaken collective awareness that raising children is not only about providing food and shelter, but also about guiding their minds, protecting their morals, and accompanying their souls, even in the virtual world. The digital world can be a blessing, but it can also be a disaster. Everything depends on the extent to which parents are present as teachers, protectors, and role models, both in real life and online. If neglect continues, not only will children's futures be threatened, but also the divine trust entrusted to them. Therefore, this journal invites all readers, especially parents, educators, and policymakers, to collectively return to the essence of Islamic parenting: parenting that is full of values, based on sharia law, and filled with responsible love. Because in this digital age, love alone is not enough; it requires direction, control, and meaningful presence.